Selected Coating Properties of Black Alder Wood as a Function of Surface Preparation, Varnish Type, Coating System and Exposure Conditions - SALCA Emilia-Adela (BOOKPI INTERNATIONAL, 2022)
Solid wood furniture still keeps its popularity on the market. Attributes such as reliability, environment-friendliness, appearance, and value are the main parameters to describe the overall quality of solid wood. Light-coloured species are preferred and black alder is one of them. Due to its workability, properties, and excellent grain orientation, black alder has the potential for furniture manufacturing. In this chapter selected coating properties of black alder as a function of surface preparation, varnish type, coating system and various exposure conditions are presented. The findings of various previous studies presented in this work could have practical applications in the furniture industry for producing value-added furniture units according to their specific conditions.
Solid wood furniture still keeps its popularity on the market. Attributes such as reliability, environment-friendliness, appearance, and value are the main parameters to describe the overall quality of solid wood. Light-coloured species are preferred and black alder is one of them. Due to its workability, properties, and excellent grain orientation, black alder has the potential for furniture manufacturing. In this chapter selected coating properties of black alder as a function of surface preparation, varnish type, coating system and various exposure conditions are presented. The findings of various previous studies presented in this work could have practical applications in the furniture industry for producing value-added furniture units according to their specific conditions.